Study of the Physical Parameters of Ordinary Portland Cement of Khyber Pakhtoon Khwa Pakistan and their comparison with Pakistan standard Specifications - Amin, Noor-ul- (Chemical Engineering Research Bulletin, 2010)
This study discusses di erent physical parameters of ordinary Portland cement (OPC) produced and available in Khyber Pakhtoon Khwa, Pakistan, and their comparison with Pakistan standards specification, which includes Blaine, compressive strength at di erent ages, consistency, setting time and Le-chatelier Expansion. All the results are presented to provide both quantitative and qualitative notion of several locally produced ordinary Portland cement of most of this constituents as determined experimentally were within the range of the standard values. The possible reasons for variation in physical parameters and their consequences have been discussed. It has been found that cherat cement is on the top in all the samples studied with reference to their physical parameters. Keywords: Ordinary Portland cement, physical parameters, quality verification DOI = 10.3329/cerb.v14i1.3729 Chemical Engineering Research Bulletin 14 (2010)7-10